Analysis of PT. X's Readiness in Fulfilling the Requirements of an Initial Public Offering (IPO) - Zabrina, Zafirah Yaffa; Triani, Ni Nyoman Alit (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Initial Public Offering (IPO) is a strategic step taken by companies to obtain long-term funding and enhance their credibility. This research is important because not all companies with growth potential are prepared to meet the complex and rigorous requirements of an IPO. The purpose of this study is to assess the readiness of PT. X in fulfilling IPO requirements from the perspectives of financial performance, corporate governance, and legal compliance. The research employs a qualitative approach using a single case embedded study method, through analysis of financial statements and in-depth interviews with internal company stakeholders. The results indicate that although the company shows stable asset and equity growth, there are inconsistencies in profit performance and several legal documents remain incomplete. In general, the company demonstrates initial steps toward IPO readiness, but still requires strategic improvements in financial stability and documentation. The conclusion of this study is that PT. X is not yet ready to conduct an IPO in the near future and must undertake comprehensive improvements, particularly in financial reporting, governance practices, and legal documentation, to meet the standards required of a public company.